Media, Technology and Sacred Narrative in Biblical Perspective - Osajie Justina Nwazuni (International Journal of Integrated Science and Technology, 2024)
This research investigated the impact of media and technology on Christian living base on sacred narrative in biblical perspective using Christian in Delta State, Nigeria as a case study. Survey method were employed and data were collected using random sampling technique to generate a population size of 400. The population were selected from Christian in churches in RCCG, winners, CGM, Anglican church, Catholic Church, Christ Embassy, MFMM, and DLCBC. 400 questionnaires were sent out, a total of 306 returned. With a mean criterion of 3.0, the statistical tools of the Statistical Package for the Social Sciences (SPSS) and Crombach Alpha correlation of 0.05 were used to analyse the study. Reviewing the impact of media and technology on Christian living base on sacred narrative in biblical perspective are: increase in spreading of the gospel of Christ, reach large/world-wide audience, access to audio-visual biblical sacred narrative that improve understanding, expansion of Christianity/church growth, fosters church communication and care in time of emergency and need, enhance worship experience and improve accessibility that also encourage young generation to actively involved in spirit edifying gospel music, access to online service when the distance involve is much, access to bible reference materials, access to sermons and devotional materials etc. The study concluded and also gave some relevant recommendations to Christians not to allow technology provides distractions that will draw them away from the main message and purpose of Christianity which is soul winning and the kingdom of God (Matt.6:33).